High-temperature-resistant sand corrosion-resistant coating and preparation method thereof
By using a high-temperature sand corrosion-resistant coating containing components such as epoxy silicone resin, chromate and zinc phosphate on the rotor of the aircraft engine high-pressure compressor, the fatigue problem caused by the impact of dust and sand particles in the high-speed airflow is solved, and significant high-temperature and corrosion-resistant effects are achieved.
Patent Information
- Application Number
- CN202411693579.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
AI Technical Summary
In extreme environments, the fatigue limit of the aircraft engine high-pressure compressor rotor decreases and even breaks due to the impact of dust and sand in high-speed airflow.
A high-temperature sand corrosion-resistant anti-corrosion coating with chemical components including epoxy silicone resin, spherical aluminum powder, strontium chromate, barium chromate, zinc phosphate, ceramic powder and vapor phase SiO2 are prepared by a specific grinding and stirring process.
This coating has good high-temperature protection, rust prevention, adhesion, heat shock resistance and salt water corrosion resistance, which significantly extends the service life of the high-pressure compressor rotor of the aircraft engine.
Smart Images

Figure CN119505700A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of modified coating preparation, and specifically relates to a high temperature resistant sand erosion and corrosion resistant coating and a preparation method thereof. Background Art
[0002] Aircraft engines are exposed to extreme temperatures, strong sunlight, salt spray and dust, and different humidity during flight. This harsh environment will accelerate the corrosion of aircraft materials. Coatings are suitable protective materials for aircraft engines. Selecting appropriate protective coatings can extend the aircraft maintenance cycle and service life, reduce maintenance costs, and ensure flight safety.
[0003] The operating temperature of the high-pressure compressor rotor of an aircraft engine is 600°C, and during use, its surface will be damaged by the impact of dust and sand in the high-speed airflow, forming pitting corrosion pits, causing the fatigue limit to drop, and even fracture. Therefore, the coating applied on it is not only required to be resistant to high temperatures and corrosion, but also requires the coating to have good adhesion to the substrate and be able to withstand the impact of high-speed airflow, that is, to have good sand erosion resistance. Summary of the invention
[0004] The purpose of the present invention is to provide a high temperature resistant sand erosion and anti-corrosion coating and a preparation method thereof, so as to solve the technical problem that the fatigue limit of the high pressure compressor rotor of an aircraft engine decreases or even breaks due to the impact of dust and sand particles in the high-speed airflow during use.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A high temperature resistant sand erosion and anti-corrosion coating comprises the following components by mass: 45-55 parts of epoxy silicone resin, 35-45 parts of spherical aluminum powder, 1-2 parts of strontium chromate, 1-2 parts of barium chromate, 2-3 parts of zinc phosphate, 5-6 parts of ceramic powder and 1.5-2.5 parts of gas-phase SiO2.
[0006] A method for preparing a high temperature resistant sand erosion and corrosion resistant coating, comprising: The pigment and ceramic powder are mixed with resin, and ground to reduce the fineness to less than 25 μm to obtain a pigment slurry; The aluminum powder is mixed and moistened with resin and then stirred to prepare an aluminum powder slurry; The fumed silica is prepared into a mother liquid with a solvent, and then mixed with a resin, and then stirred to prepare a thixotropic agent sol; The pigment slurry, aluminum powder slurry, thixotropic agent sol and resin are mixed evenly, and a solvent is added to adjust the viscosity to prepare the coating.
[0007] Preferably, grinding is performed using a cone mill at a speed of 160 to 180 r / min.
[0008] Preferably, the grinding time is 20-30 minutes.
[0009] Preferably, the aluminum powder is mixed and moistened with the resin and then stirred at a stirring speed of 3000 to 4000 r / min.
[0010] Preferably, the stirring time is 10-20 minutes.
[0011] Preferably, the fumed silica is prepared into a mother liquor with a solvent, and then mixed with the resin, and then stirred at a stirring speed of 2000 to 3000 r / min for 8 to 10 minutes.
[0012] Preferably, the solvent is a mixed solution of acetone and xylene.
[0013] Preferably, the pigment slurry, aluminum powder slurry, thixotropic agent sol and resin are stirred evenly at a stirring speed of 3000-4000 r / min for 5-10 minutes.
[0014] Preferably, a solvent is added to adjust the viscosity, and the viscosity range is: 15-20s.
[0015] Compared with the prior art, the present invention has the following beneficial effects: the present invention provides a high-temperature sand-erosion resistant anti-corrosion coating, which adopts epoxy silicone resin to have good high-temperature protection effect, adds strontium chromate and barium chromate to the coating to have good anti-rust effect, adds zinc phosphate to the coating to have strong adhesion to the metal substrate, and the ceramic powder in the coating can improve its thermal stability, prolong the heat-resistant time, and obtain better adhesion, gloss, heat shock resistance and salt water corrosion resistance. The combination of zinc phosphate and chromate pigment has the effect of forming a corrosion-inhibiting complex with Fe2+, and can enhance the effect of anode passivation together with chromate pigment. The anti-rust effect of zinc phosphate is often slowly manifested through the moisture permeability of the coating after film formation, and the addition of chromate helps to provide an early anti-rust effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The present invention is a flow chart of a method for preparing a high temperature resistant sand erosion and anti-corrosion coating. DETAILED DESCRIPTION
[0017] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0018] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0019] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0020] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0021] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0022] The invention provides a high temperature resistant sand erosion and corrosion resistant coating, which uses epoxy silicone resin as a resin matrix, strontium chromate, barium chromate, zinc phosphate, spherical aluminum powder and ceramic powder as pigments and fillers, and is supplemented with a gas phase SiO2 thixotropic agent and a proper amount of mixed solvent.
[0023] Its chemical components include the following components by mass: epoxy silicone resin (industrial grade, solid content ≥50%): 45-55 parts, spherical aluminum powder (Φ5-10μm, purity not less than 99%): 35-45 parts, strontium chromate (industrial grade): 1-2 parts, barium chromate (chemically pure): 1-2 parts, zinc phosphate (chemically pure): 2-3 parts, ceramic powder (industrial grade): 5-6 parts, gas-phase SiO2 (industrial grade): 1.5-2.5 parts.
[0024] Among organic resins, silicone has the best temperature resistance, which can work at 180℃~250℃ for a long time and 350℃ for a short time. In order to improve the solvent resistance, adhesion and mechanical properties of silicone resin, it is usually modified with epoxy resin to form a stable silicon-oxygen-carbon chain. The introduction of a highly thermally stable -Si-O-C- skeleton into the main chain of the resin will further form a -Si-O-Al- bond with the aluminum powder in the coating, thereby playing a role in high temperature protection.
[0025] The addition of epoxy resin improves many problems of silicone coatings. The resulting epoxy silicone resin has the advantages of both epoxy resin and silicone resin. It not only improves heat resistance, but also has good corrosion resistance and outstanding adhesion, which significantly improves the performance of the coating and reduces costs at the same time.
[0026] Chromate pigments are widely used in anti-rust paints and maintenance primers for both steel and light metals. Their main anti-rust effect is to dissociate CrO4 due to their solubility in water. 2- The iron is passivated at the anode. At the same time, the series of reduction effects of hexavalent chromium in the cathode area help to eliminate the hydrogen peroxide produced in the cathode reaction. It forms a stable compound with iron and has a significant passivation effect on metal corrosion. Strontium chromate is a neutral pigment with a pH of ≈ 7 and a large solubility. Due to its good light resistance and high thermal stability (no decomposition when directly heated to 1000°C), it can achieve good corrosion inhibition effects under drastic climate changes and high surface temperatures. Barium chromate is the least water-soluble of the chromate pigments. When a pigment with very low solubility is used alone, due to the CrO4 2- If the concentration is insufficient, the residual moisture on the metal surface under the paint film will first cause local corrosion. If it is used in combination with chromates with higher solubility, a satisfactory anti-rust effect can be achieved. Therefore, barium chromate is often used in combination with chromates with higher solubility to provide accumulation of chromate ions. In addition, it is a neutral pigment like strontium chromate with high thermal stability (its own decomposition temperature can also reach 1000℃).
[0027] Zinc phosphate is a commonly used anti-rust pigment for heat-resistant coatings, and its anhydrous salt has a melting point of up to 900°C. In addition to low / non-toxicity, zinc phosphate also has the following advantages: white or light color, low refractive index, so it is very easy to color; it can be dispersed in various base materials such as oily resin type and water-based; the coating prepared with it has good construction performance and has strong adhesion to metal substrates or topcoat coatings; the raw materials are easily available and the price is moderate.
[0028] The combined use of zinc phosphate and chromate pigments has the following advantages: (1) Zinc phosphate to Fe 2+ It has the function of forming corrosion inhibition complex and can enhance the anodic passivation effect together with chromate pigments.
[0029] (2) The anti-rust effect of zinc phosphate often manifests itself slowly through the moisture permeability of the coating after film formation. The addition of chromate helps to provide an early anti-rust effect.
[0030] (3) Zinc phosphate combines with chromate pigments to form heteropolyacids, which can then react with Fe in active rust. 3+ It forms inhibitory complexes and stabilizes rust.
[0031] The ceramic powder in the coating has a great influence on the performance of the coating. From the time when the painted parts enter the furnace and the organic film-forming substances are decomposed and carbonized by heat, to the entire process when the parts work under high temperature and thermal corrosion conditions, the ceramic powder always bears the important role of forming a stable and dense film layer at high temperature to prevent oxidation and decarburization. That is, when the organic film-forming substances lose their adhesion due to decomposition at a certain temperature, the ceramic powder takes over the organic film-forming substances to exert the adhesion and film-forming properties on the pigments and base metals, forming a new dense layer to withstand the effects of thermal oxidation, corrosion and air flow scouring at high temperatures. In short, the addition of ceramic powder in the heat-resistant coating will improve its thermal stability, extend the heat-resistant time, and obtain better adhesion, gloss, heat shock resistance and salt water corrosion resistance.
[0032] Gas phase SiO2 is produced by hydrolysis of SiCl4 in a hydrogen-oxygen flame. It has a small particle size (about 0.015 μm in diameter), a large specific area (190 to 460 m2 of surface area per gram of SiO2), and silanol groups on the surface. These silanol groups can interact with adjacent gas phase SiO2 particles to form hydrogen bonds. The structure thus formed produces a thickening effect in the coating. Under shear force, hydrogen bonds are destroyed and the viscosity decreases; when the shear force is eliminated, hydrogen bonds are re-formed, the structure is formed again, and the viscosity increases again, thus presenting thixotropy. As an important construction process performance, thixotropy has the following main functions: the coating can be thicker at one time; it can be easily applied during construction, but when the application stops, the vertical surface coating will not sag, and it can effectively prevent precipitation during storage.
[0033] like Figure 1 The present invention also provides a method for preparing a high temperature resistant sand erosion and corrosion resistant coating, comprising the following steps: (1) Preparation of pigment slurry The pigment, ceramic powder and other components are blended with part of the resin, and ground with a conical mill at a speed of 160-180 r / min for 20-30 minutes to reduce the fineness to below 25 μm to obtain a pigment slurry.
[0034] (2) Preparation of aluminum slurry The aluminum powder is mixed and moistened with part of the resin, and stirred with a high-speed disperser at a speed of 3000-4000 r / min for 10-20 minutes to prepare an aluminum powder slurry.
[0035] (3) Preparation of thixotropic agent sol A certain amount of solvent is used to prepare part of the fumed silica into a mother liquor, which is then blended with part of the resin. A high-speed disperser is then used to stir the mother liquor at a speed of 2000 to 3000 r / min for 8 to 10 minutes to fully disperse the mother liquor to prepare a thixotropic agent sol.
[0036] (4) Preparation of coating The pigment slurry, aluminum powder slurry, thixotropic agent sol and remaining resin are stirred in a high-speed disperser at a speed of 3000-4000r / min for 5-10 minutes to be fully mixed, and then a proper amount of solvent is added to adjust the viscosity to a suitable value (15s-20s) to prepare the coating.
[0037] The performance of the solvent directly affects the characteristics, viscosity and drying time of the coating, and should be formulated according to the volatilization rate, construction process and curing conditions. Generally, a mixed solvent is used because the volatilization rate of the mixed solvent with different boiling points is relatively balanced during the film formation process, and it can form a uniform and well-spread coating. In addition, in addition to volatility and solubility, factors such as the flash point and flammability of the solvent, toxicity and resource price should also be considered. Based on the above aspects, the solvent is selected. Since xylene is a common solvent for silicone resin and acetone is a common solvent for epoxy resin, acetone and xylene are preferred as solvents. The specific evaporation rate of acetone is 720 and the boiling point is 56.1℃. The specific evaporation rate of xylene is 68 and the boiling point is 135.0℃. Compared with the two, xylene is less volatile. When xylene is used alone as a solvent, after the prepared coating is sprayed on the surface of the test piece, the solvent evaporates slowly, resulting in a long surface drying time, and the coating is easily affected by external factors, resulting in a decrease in the surface finish of the film. Moreover, the irritating smell and toxicity of xylene are high, which will damage the health of the construction workers and is not conducive to environmental protection. If acetone is used alone as a solvent, the organic silicon component in the base resin is not well soluble in acetone, and the prepared coating has poor processability. Moreover, since acetone evaporates quickly in the air, bubbles are likely to appear on the coating surface after spraying. Therefore, a mixed solvent of acetone and xylene is selected as the solvent system of the coating.
[0038] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0039] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0040] Embodiment 1: The present embodiment provides a high temperature resistant sand erosion and anti-corrosion coating, whose chemical components include the following components in parts by mass: epoxy silicone resin (industrial grade, solid content ≥50%): 50 parts, spherical aluminum powder (Φ5~10μm, purity not less than 99%): 38 parts, strontium chromate (industrial grade): 1 part, barium chromate: (chemically pure): 1 part, zinc phosphate (chemically pure): 2 parts, ceramic powder (industrial grade): 6 parts, gas-phase SiO2 (industrial grade): 2 parts.
[0041] This embodiment also provides a method for preparing a high temperature resistant sand erosion and corrosion resistant coating, comprising the following steps: (1) Preparation of pigment slurry The pigment, ceramic powder and other components are blended with part of the resin, and ground with a conical mill at a speed of 170 r / min for 30 minutes to reduce the fineness to less than 25 μm to obtain a pigment slurry.
[0042] (2) Preparation of aluminum slurry The aluminum powder was mixed and moistened with part of the resin, and stirred at a speed of 3500 r / min for 20 minutes using a high-speed disperser to prepare an aluminum powder slurry.
[0043] (3) Preparation of thixotropic agent sol A certain amount of solvent is used to prepare part of the fumed silica into a mother liquor, which is then blended with part of the resin, and then fully dispersed by stirring at a speed of 2500r / min for 10 minutes using a high-speed disperser to prepare a thixotropic agent sol.
[0044] (4) Preparation of coating The pigment slurry, aluminum powder slurry, thixotropic agent sol and remaining resin are stirred in a high-speed disperser at a speed of 3500r / min for 10 minutes to be fully mixed, and then a proper amount of solvent is added to adjust the viscosity to a suitable value (15s-20s) to prepare the coating.
[0045] Spray one layer of the well-stirred coating on a mild steel test piece (degrease the test piece with aviation washing gasoline and then sandblast with 120-220 mesh alumina) and air dry for at least 10 minutes to form a matte gray surface; then spray a second layer and air dry for at least 10 minutes. Place the test piece in a forced air drying oven and bake at (150±5)℃ for 1 hour. The dry film thickness is 25-100μm. Then place the test piece in a medium temperature furnace and heat treat at (560±5)℃ for 2 hours. Cool to room temperature. The paint film should be uniform and free of peeling and cracks. Spray the coating on the back of the prepared test piece (pay attention to protect the test surface of the sample) and bake at (150±5)℃ for 1 hour. The baked sample should be placed in an environment with a temperature of (23±2)℃ and a relative humidity of (50±5)% for at least 16 hours.
[0046] The coating was tested according to the MSRR 9253 material standard, and the results are as follows: Adhesion: Level 0 Conductivity: Conductive Temperature resistance: (600±5)℃×100h, the paint film does not crack, bubble or fall off.
[0047] Resistance to synthetic seawater thermal cycle: (450±5)℃×2h, spray seawater for 20h after cooling as one cycle, a total of 10 cycles, the paint film has no peeling, bubbles, and no corrosion spread.
[0048] Resistant to 4050 synthetic lubricating oil: (150±5)℃×100h, the paint film does not bubble or soften.
[0049] Resistance to RP-3 fuel: (70±2)℃×100h, the paint film does not bubble or soften.
[0050] The high temperature sand erosion resistance comparison test was conducted with PL219 coating (imported), SermetelW coating (imported), and HYF-14 coating (domestic). The results are as follows: The four coatings are ranked from best to worst in order of PL219 coating (imported), a high temperature erosion resistant anti-corrosion coating, HYF-14 coating (domestic), and SermetelW coating (imported). Moreover, the high temperature erosion resistance of a high temperature erosion resistant anti-corrosion coating is much better than that of HYF-14 coating (domestic) and SermetelW coating (imported), and has almost the same high temperature erosion resistance as PL219 coating (imported).
[0051] Embodiment 2: The present embodiment provides a high temperature resistant sand erosion and anti-corrosion coating, whose chemical components include the following components by mass: epoxy silicone resin (industrial grade, solid content ≥50%): 45 parts, spherical aluminum powder (Φ5~10μm, purity not less than 99%): 45 parts, strontium chromate (industrial grade): 2 parts, barium chromate: (chemically pure): 2 parts, zinc phosphate (chemically pure): 3 parts, ceramic powder (industrial grade): 5 parts, gas-phase SiO2 (industrial grade): 1.5 parts.
[0052] This embodiment also provides a method for preparing a high temperature resistant sand erosion and corrosion resistant coating, comprising the following steps: (1) Preparation of pigment slurry The pigment, ceramic powder and other components are blended with part of the resin, ground with a conical mill at a speed of 160 r / min for 20 minutes to reduce the fineness to less than 25 μm, and obtain a pigment slurry.
[0053] (2) Preparation of aluminum slurry The aluminum powder was mixed and moistened with part of the resin, and stirred with a high-speed disperser at a speed of 3000 r / min for 15 minutes to prepare an aluminum powder slurry.
[0054] (3) Preparation of thixotropic agent sol A certain amount of solvent is used to prepare part of the fumed silica into a mother liquor, which is then blended with part of the resin, and then fully dispersed by stirring at a speed of 2000 r / min for 9 minutes using a high-speed disperser to prepare a thixotropic agent sol.
[0055] (4) Preparation of coating The pigment slurry, aluminum powder slurry, thixotropic agent sol and remaining resin are fully mixed by stirring at a speed of 3000r / min for 8 minutes in a high-speed disperser, and then a proper amount of solvent is added to adjust the viscosity to a suitable value (15s-20s) to prepare the coating.
[0056] Embodiment 3: The present embodiment provides a high temperature resistant sand erosion and anti-corrosion coating, whose chemical components include the following components by mass: epoxy silicone resin (industrial grade, solid content ≥50%): 55 parts, spherical aluminum powder (Φ5~10μm, purity not less than 99%): 35 parts, strontium chromate (industrial grade): 1 part, barium chromate: (chemically pure): 2 parts, zinc phosphate (chemically pure): 3 parts, ceramic powder (industrial grade): 5 parts, gas-phase SiO2 (industrial grade): 2.5 parts.
[0057] This embodiment also provides a method for preparing a high temperature resistant sand erosion and corrosion resistant coating, comprising the following steps: (1) Preparation of pigment slurry The pigment, ceramic powder and other components are blended with part of the resin, and ground with a conical mill at a speed of 180 r / min for 30 minutes to reduce the fineness to less than 25 μm to obtain a pigment slurry.
[0058] (2) Preparation of aluminum slurry The aluminum powder was mixed and moistened with part of the resin, and stirred with a high-speed disperser at a speed of 4000 r / min for 20 minutes to prepare an aluminum powder slurry.
[0059] (3) Preparation of thixotropic agent sol A certain amount of solvent is used to prepare part of the fumed silica into a mother liquor, which is then blended with part of the resin, and then fully dispersed by stirring at a speed of 3000r / min for 8 minutes using a high-speed disperser to prepare a thixotropic agent sol.
[0060] (4) Preparation of coating The pigment slurry, aluminum powder slurry, thixotropic agent sol and remaining resin are fully mixed by stirring at a speed of 3000r / min for 5 minutes in a high-speed disperser, and then a proper amount of solvent is added to adjust the viscosity to a suitable value (15s-20s) to prepare the coating.
[0061] From the above embodiments, the high temperature resistant sand erosion and anti-corrosion coating prepared by the present invention has good construction process performance, excellent adhesion, high temperature resistance, resistance to aviation media, resistance to seawater corrosion, and resistance to high temperature sand erosion.
[0062] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A high temperature resistant sand erosion and corrosion resistant coating, characterized in that: The invention comprises the following components by weight: 45-55 parts of epoxy silicone resin, 35-45 parts of spherical aluminum powder, 1-2 parts of strontium chromate, 1-2 parts of barium chromate, 2-3 parts of zinc phosphate, 5-6 parts of ceramic powder and 1.5-2.5 parts of gas-phase SiO2.
2. A method for preparing a high temperature resistant sand erosion and corrosion resistant coating according to claim 1, characterized in that: include: The pigment and ceramic powder are mixed with resin, and ground to reduce the fineness to less than 25 μm to obtain a pigment slurry; The aluminum powder is mixed and moistened with resin and then stirred to prepare an aluminum powder slurry; The fumed silica is prepared into a mother liquid with a solvent, and then mixed with a resin, and then stirred to prepare a thixotropic agent sol; The pigment slurry, aluminum powder slurry, thixotropic agent sol and resin are mixed evenly, and a solvent is added to adjust the viscosity to prepare the coating.
3. The method for preparing a high temperature resistant sand erosion and anti-corrosion coating according to claim 2, characterized in that: The grinding is carried out using a conical mill at a speed of 160 to 180 r / min.
4. The method for preparing a high temperature resistant sand erosion and anti-corrosion coating according to claim 3, characterized in that: The grinding time is 20-30 minutes.
5. The method for preparing a high temperature resistant sand erosion and anti-corrosion coating according to claim 2, characterized in that: The aluminum powder is mixed and moistened with resin and then stirred at a stirring speed of 3000 to 4000 r / min.
6. The method for preparing a high temperature resistant sand erosion and anti-corrosion coating according to claim 5, characterized in that: The stirring time is 10-20 minutes.
7. The method for preparing a high temperature resistant sand erosion and anti-corrosion coating according to claim 2, characterized in that: The fumed silica is prepared into a mother liquor with a solvent, and then mixed with a resin, and then stirred at a speed of 2000-3000 r / min for 8-10 minutes.
8. The method for preparing a high temperature resistant sand erosion and anti-corrosion coating according to claim 7, characterized in that: The solvent used was a mixed solution of acetone and xylene.
9. The method for preparing a high temperature resistant sand erosion and anti-corrosion coating according to claim 2, characterized in that: The pigment slurry, aluminum powder slurry, thixotropic agent sol and resin are stirred evenly at a stirring speed of 3000-4000 r / min for 5-10 minutes.
10. The method for preparing a high temperature resistant sand erosion and anti-corrosion coating according to claim 2, characterized in that: Add solvent to adjust the viscosity, the viscosity range is: 15-20s.
Citation Information
Patent Citations
High-temperature-resistant heat-proof paint and preparation and use methods thereof
CN102464939A
Special high-temperature resisting coating for die casting machine
CN107841244A